Latilactobacillus sakei Furu2019 and stachyose as probiotics, prebiotics, and synbiotics alleviate constipation in mice - Guo, Yanan; Song, Liqiong; Huang, Yuanming; Li, Xianping; Xiao, Yuchun; Wang, Zhihuan; Ren, Zhihong (Frontiers in Nutrition, 2023)
Slow transit constipation (STC) is a common disorder in digestive system. The aim of this study was to evaluate the effects of stachyose (ST) and Lactobacillus sakei Furu 2019 (L. sakei) alone or combination on diphenoxylate-induced constipation and explore the underlying mechanisms using a mouse model. ICR mice were randomly divided into 5 groups. The normal and constipation model groups were intragastrically administrated with PBS. The prebiotic, probiotic, and synbiotic groups were intragastrically administrated with ST (1.5 g/kg bodyweight), alive L. sakei (3×109 CFU/mouse), or ST + L. sakei, respectively. After 21 days of interventions, all mice except the normal mice were intragastrically administrated with diphenoxylate (10 mg/kg bodyweight). Defecation indexes, constipation-related intestinal factors, serum neurotransmitter and hormone levels, short-chain fatty acids (SCFAs) and intestinal flora were measured. Our results showed that three treatments with prebiotic ST, probiotic L. sakei, and synbiotic combination (ST + L. sakei) all alleviated constipation, and symbiotic treatment was superior to prebiotic or probiotic treatment alone in some defecation indicators. The RT-PCR and immunohistochemical experiments showed that all three treatments relieved constipation by affecting aquaporins (AQP4 and AQP8), interstitial cells of Cajal (SCF and c-Kit), glial cell-derived neurotrophic factor (GDNF), and Nitric Oxide Synthase (NOS). The symbiotic treatment significantly increased activity of serum excitatory neurotransmitters and hormones (5-hydroxytryptamine, substance P, motilin), and reduced activity of serum inhibitory neurotransmitters (vasoactive intestinal peptide, endothelin). The result of 16S rDNA sequencing of feces showed that synbiotic treatment with ST and L. sakei significantly increased the relative abundance of beneficial bacteria such as Akkermansia, and regulate the intestinal flora of STC mice. In conclusion, both prebiotic ST and probiotic L. sakei are effective to relieve constipation and their combination has a better therapeutic effect on STC as a potential synbiotics.